Micro-RNAs in abdominal aortic aneurysms: insights from animal models and relevance to human disease. Issue 2 (10th March 2016) - Raffort, Juliette; Lareyre, Fabien; Clement, Marc; Mallat, Ziad
Abstract: Abdominal aortic aneurysm (AAA) is a major health concern and may be associated with high rates of mortality linked to acute complications. Diagnosis and treatment are, respectively, based on imaging and surgical techniques. Drug-based therapies are still mostly ineffective, which highlight a real unmet need. Major pathophysiological mechanisms leading to aneurysm formation involve inflammatory processes, degradation of the extracellular matrix, and loss of smooth muscle cells. However, the precise cellular and molecular pathways are still poorly understood. Recently, microRNAs have emerged as major intracellular players in a wide range of biological processes, and their stability in extracellular medium within microvesicles has led to propose them as mediators of intercellular crosstalk and as potential biomarkers and therapeutic targets in a variety of disease settings. To date, several studies have been performed to address the involvement of micro-RNAs (miRs) in aneurysm formation and complications. Here, we discuss the roles and implications of miRs in animal models and their relevance to human AAA.